Evaluation of the Influence Caused by Tunnel Construction on Groundwater Environment: A Case Study of Tongluoshan Tunnel, China - Jian Liu; Dan Liu; Kai Song (Advances in Materials Science and Engineering)
Problems related to water inflow during tunnel construction are challenging to designers, workers, and management departments, as they can threaten tunneling project from safety, time, and economic aspects. Identifying the impacts on groundwater environment resulting from tunnel drainage and making a correct assessment before tunnel construction is essential to better understand troubles that would be encountered during tunnel excavation and helpful to adopt appropriate countermeasures to minimize the influences. This study presents an indicator system and quantifies each indicator of Tongluoshan tunnel, which is located in southwest China with a length of 5.2 km and mainly passes through carbonate rocks and sandstones, based on field investigation and related technological reports. Then, an evaluation is made using fuzzy comprehensive assessment method, with a result showing that it had influenced the local groundwater environment at a moderate degree. Information fed back from environmental investigation and hydrologic monitoring carried out during the main construction period proves the evaluation, as the flow of some springs and streams located beside the tunnel route was found experiencing an apparent decline.